Comparative efficacy and safety of hypnotics for insomnia in older adults: a systematic review and network meta-analysis. Issue 5 (29th November 2020) - Chiu, Hsiao-Yean; Lee, Hsin-Chien; Liu, Jen-Wei; Hua, Shi-Jun; Chen, Pin-Yuan; Tsai, Pei-Shan; Tu, Yu-Kang
Abstract: Study Objectives: To compare the efficacy and safety of various hypnotics for identifying the best treatments for insomnia in older adults. Methods: We searched the EMBASE, PubMed, ClinicalTrials.gov, and ProQuest Dissertations and Theses A&I databases from the inception to September 12, 2020. Only randomized controlled trials comparing hypnotics with either another hypnotic or placebo for insomnia treatment in elderly people were included. Sleep outcomes, including total sleep time, sleep onset latency, wake after sleep onset, sleep efficiency, were derived from polysomnography, valid questionnaires, or sleep diaries. Results: We identified 24 articles with 5917 older adults. Eszopiclone and low-dose doxepin were ranked the optimal therapy for prolonging objective and subjective total sleep time (26.69 and 28.19 min), respectively, compared to placebo. Zaleplon was the most effective therapy in reducing objective and subjective sleep onset latency (–21.63 and –15.86 min) compared with control. Temazepam was the best treatment for objective and subjective wake after sleep onset (–25.29 and –22.25 min) compared with control. Low-dose doxepin appeared to be the effective treatment for increasing objective sleep efficiency (6.08%) Triazolam showed the higher risk of overall adverse events (odds ratio, 1.96, 95% confidence interval 1.03–3.74) when compared to zaleplon. Conclusions: Considering study quality and the potential adverse effects of benzodiazepines and nonbenzodiazepines, low-dose doxepin seems to be the optimal pharmacotherapy for the improvements in total sleep time and sleep efficiency. Future RCTs investigating the treatment effects of hypnotics, particularly low-dose doxepin, on insomnia in older adults are warranted. PROSPERO Registration number: CRD42016046301.